Church colleges research project: interim papers - Gay, J; Lazenby, D (Culham College Institute, 1985)
Each of these papers, apart from paper 3, contains the detailed results from the questionnaires sent to each of the constituent groups taking part in the Church Colleges Research Project. These results formed the basis for the analyses in the final report. A view from the General Synod, the Board of Education and the Diocesan Directors of Education A view from Church schools and theological colleges A preliminary theological critique The first year students The third year and PGCE students The college staff A view from the head teachers of teaching practice schools Each of the reports was used as promised feedback to the relevant group and also made available more widely to those who wished for copies. In the reports on the questionnaire results from the students and staff, it was agreed that the results could be itemised by college but that the college names would be anonymised. It was also agreed that each college would be sent its own results for internal use. Unfortunately, the key to the names appears not to have been retained once the project was completed.